IDENTIFICATION OF JUVENILES OF THREE SPECIES OF METAPENAEUS (DECAPODA, PENAEIDAE) - Rao, P Vedavyasa (Indian Journal of Fisheries, 2011)
Distinguishing characters of juveniles (10 to 27 mm body length) of three speciesof commercially important prawns, namely, Metapenaeus dobsoni, M. nionocerosand M. affinis are described. Colouration of body, distribution pattern of chromatophoreson carapace and abdominal segments, and length of rostrum of each of the speciesare compared. A key for their identification is provided based on these characters.